Training Model Design Terrarium to Increase Teachers Special Education Competency - Asriwijiastuti; Masitoh, Siti; Ardianingsih, Febrita (Universitas Pendidikan Ganesha, 2024)
Special education teachers with non-science backgrounds were found to have 85% below standard and weak competency in explaining environmental phenomena related to ecosystem concepts and experiments. This condition requires conscious efforts to enhance quality through modeling and direct experimentation. This study aims to analyze the improvement of teacher competencies in creating terrariums by applying a training model based on